ANALISIS KEBIJAKAN POLITIK PENDIDIKAN ISLAM DALAM PENGEMBANGAN KEBIJAKAN PUBLIK - Intan Permatasari Nasution; Ahmad Burhanuddin (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
When it comes to education policy, the political situation is very important. The link between education and state politics is very strong because education educates its citizens to become useful and successful citizens.  Politics and education are two important components of the socio-political structure of every country, both developed and developing. Often considered as different parts that are not related to each other. Although both play an important role in the process of creating the characteristics of a national society. Public policy is a highly complex, political, and analytical process that has no beginning or end point. There are times when the complex combination of factors known as policymaking produces an outcome called a policy. The first step in policy making is to find a general area, conduct analysis, set targets, decide on areas of implementation, negotiate and consult on political and societal aspects, and finally produce and implement a final policy.  To avoid conflict and increase the chances of achieving organizational goals, effective policymaking involves agreeing on goals at all levels.